2015
DOI: 10.1016/j.prevetmed.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting dairy farmers’ attitudes towards antimicrobial medicine usage in cattle in England and Wales

Abstract: There has been growing concern about bacterial resistance to antimicrobials in the farmed livestock sector. Attention has turned to sub-optimal use of antimicrobials as a driver of resistance. Recent reviews have identified a lack of data on the pattern of antimicrobial use as an impediment to the design of measures to tackle this growing problem. This paper reports on a study that explored use of antibiotics by dairy farmers and factors influencing their decision-making around this usage. We found that respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
202
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(229 citation statements)
references
References 31 publications
20
202
4
3
Order By: Relevance
“…Farm veterinarians, because of their knowledge of pathogens and disease as well as of the 64 specific characteristics and circumstances of individual farms and farmers, should therefore be ideally 65 positioned to advise effectively on individually-tailored biosecurity strategies. While it has been 66 reported that the preferred and most influential source of advice for many farmers is their own vet 67 (Brennan and Christley, 2013;Jones et al, 2015), it has also been acknowledged that veterinary advice 68 is not always followed even when perceived to be useful by farmers (Brennan and Christley, 2013). 69…”
Section: Introduction 35mentioning
confidence: 99%
“…Farm veterinarians, because of their knowledge of pathogens and disease as well as of the 64 specific characteristics and circumstances of individual farms and farmers, should therefore be ideally 65 positioned to advise effectively on individually-tailored biosecurity strategies. While it has been 66 reported that the preferred and most influential source of advice for many farmers is their own vet 67 (Brennan and Christley, 2013;Jones et al, 2015), it has also been acknowledged that veterinary advice 68 is not always followed even when perceived to be useful by farmers (Brennan and Christley, 2013). 69…”
Section: Introduction 35mentioning
confidence: 99%
“…In a survey of pork producers carried out by ADAS a decade ago, 90 per cent of farmers thought that the situation of medicines use on farms was acceptable (Wheeler 2014), even though many in the public sphere feel that AMs are drastically overused in animal agriculture, including pig production (Morris and others 2016). More recent studies show up to 90 per cent of dairy farmers believe they are following best practice, while almost half are unaware of advice such as the Responsible Use of Medicines in Agriculture Alliance (RUMA) guidelines (Jones and others 2015, RUMA 2015). Farmers in a 2016 Royal Association of British Dairy Farmers survey, however, overwhelmingly saw the current antibiotic resistance crisis as something they (along with their vets) need to play a part in tackling (unpublished data).…”
Section: The Problemmentioning
confidence: 99%
“…However, this is something that industry is taking seriously. In a more recent UK survey of dairy farmers (Jones and others 2015), 100 per cent of respondents had either reduced or planned to reduce antibiotic use. Seventy per cent thought that reducing antibiotic usage was a good thing to do, with veterinary surgeons being the most influential source of information.…”
Section: Responsible Usementioning
confidence: 99%
“…Seventy per cent thought that reducing antibiotic usage was a good thing to do, with veterinary surgeons being the most influential source of information. Farmers who received a greater proportion of their income from milk production or who were more likely to remain in milk production were more likely to demonstrate a positive intention to reduce antibiotic use (Jones and others 2015). This demonstrates that there is clear recognition among dairy farmers that this is an important aspect of herd health management (HHM) and veterinary surgeons are well placed to drive change in this area.…”
Section: Responsible Usementioning
confidence: 99%